Spatial–temporal variation of daily precipitation in different levels over mainland China during 1960–2019 - Kexin Zhang; Tiangui Wang; Li Zhao; Jiaoting Peng; Yan Ji (Meteorological Applications)
Abstract Precipitation, essential for the water cycle and key to surface runoff and groundwater, causes floods and droughts when unevenly distributed. Understanding the variations in precipitation across China is vital for managing water resources and preventing weather‐related disasters. In this study, we analyzed the spatial–temporal variations in rainfall amounts and the number of rainy days across different levels in China using daily precipitation data during 1960–2019. We found a nonsignificant increase in annual total precipitation (ATP), but a significant decline in the number of days with ATP during this period. This shift suggests that precipitation is becoming more concentrated in fewer days, potentially due to an increase in the frequency of heavy rain (25 ≤ p < 50 mm/day, L3), rainstorm (50 ≤ p < 100 mm/day, L4), and heavy rainstorm (p > 100 mm/day, L5). The amount and frequency of precipitation in light rain (0.1 ≤ p < 10 mm/day, L1) and moderate rain (10 ≤ p < 25 mm/day, L2) exhibited a decreasing trend during this period, whereas the patterns for L3, L4, and L5 demonstrated an increasing trend. Notably, the decrease in the number of days with L1 and L2 precipitation was relatively minor compared with the substantial increase in the number of days experiencing L3, L4, and L5 precipitation. Despite L1 precipitation making up only 24.9% of China's ATP, it accounts for 78.6% of total precipitation days. This underscores the important role played by L1 precipitation events in determining the overall frequency of precipitation occurrences in China. Significant regional disparities are observed in both precipitation amounts and the number of precipitation days across different precipitation levels. Furthermore, large‐scale climate indices have consistently affected China's precipitation patterns since 1960, impacting not just the current year but possibly extending into the subsequent year.